Growth of non-polar (11-20) a-plane GaN based leds grown on (1-120) r-plane sapphire substrate via MOCVD / Anas Kamarundzaman - Anas , Kamarundzaman (2022)
Conventional gallium nitride (GaN)-based light-emitting diodes (LEDs), commonly grown in the c-plane direction suffer from the huge built-in electric field from spontaneous and piezoelectric polarisation, which cause the energy-band bending in the energy band diagram. Motivated to avoid the undesirable polarisation effect, this study explored the growth of the non-polar (11–20) a-plane GaN. In this study, the full structure of the a-plane InGaN/GaN LED epitaxial was grown on a two-inch r-plane sapphire substrate using Taiyo Nippon Sanso SR-2000 metal-organic chemical vapour deposition (MOCVD). The LED’s structure consisted of four main layers, which were undoped gallium nitride (ud-GaN), n-type GaN, p-type GaN and the active region of InGaN/GaN multi-quantum well (MQW). Several optimisations were employed in the epitaxial growth of ud-GaN, which were the GaN nucleation layer, the V/III ratio and the insertion of the periodic AlN/GaN multilayers (MLs) at different positions, as well as the number of AlN/GaN ML pairs. The a-plane ud-GaN with a low-temperature nucleation layer (NL), a low V/III ratio and 120 pairs of AlN/GaNMLs showed the best crystalline quality with the full width at half maximum (FWHM) value of 756 arcsec and surface roughness of 2.15 nm from the X-ray rocking curve (XRC) scan. The n- and p-type GaN were tuned by varying the flow rates of disilane and Cp2Mg, respectively. Both n- and p-type GaN showed the best electrical properties at the highest doping flow rate, with carrier concentration and mobility of 4.94 × 1019 cm-³ and 58.39 cm2/V•s for the n-GaN, respectively, and 2.13 × 1018 cm-³ and 20.46 cm2/V•s for the p-GaN, respectively. The full a-plane InGaN/GaN LED was grown on top of different ud-GaN structures, while utilising the suitable n- and p-type GaN. Significant improvements in light output power from 10 μW at 100 mA to 70 μW were recorded when the growth of the InGaN/GaN LED utilised 120 pairs of AlN/GaN MLs.